Creating awareness and understanding in implementing Green Construction / Intan Rahani Endut - Endut, Intan Rahani (2013)
Construction Industry Environmental issues are now the most important issue in the twentyfirst century. Traditional construction not only consumes large resources, but also does harm to the environment. Most of enterprises only concern about green construction on the surface level, the reduction of construction noise, disturbance to residents and environmental pollution. The green construction is understood incomprehensively and incompletely, and relevant technology is accepted passively. Moreover, the construction is still conducted with traditional thinking model and standard. Subsequently, it is unable to utilize appropriate technology and scientific management mode in the whole process management of green construction systematically. In Malaysia, there is no standard risk management framework for green construction. Therefore, this research intends (1) To identify the comprehensive management and procedures improvement of the environmental influence on the green construction and (2) To develop and validate a Risk Management Action Plan (RMAP) for green construction. The research methodology applied in this research includes literature reviews, questionnaires and interviews. It is found that although there are some forms of risk management systems being used in the Malaysian construction industry, most of them are not well structured, documented and implemented in a formal manner. Therefore, the idea of establishing the Environmental Risk Management Action Plan (RMAP) for Malaysian Green Construction is paramount and cannot be over emphasized. It is in line with the Strategic Reform Initiatives (SRI) under National Economic Model as the government intends to create a competitive domestic economy and ensure the sustainability of growth.